An urban composite development index based on China's five development concepts. Issue 2 (14th March 2020) - Tan, Khee Giap; Zhang, Xuyao; Song, Lin
Abstract : Purpose: Shandong is a thriving economic centre, being the third largest province by land area in China. It also has the second largest resident population of 99, 470, 000 and the third largest gross regional domestic product of RMB 6.8tn in 2016. The urbanisation rate of Shandong has been quickly expanding from 45 per cent in 2005 to 58 per cent in 2016. This paper aims to examine the urban development, performance and liveability of 17 Shandong cities through areas such as infrastructure, public services, education and environmental protection. Design/methodology/approach: Building upon the theoretical underpinnings of China's five development concepts – innovation, coordination, green development, opening up and sharing, this paper has constructed the inaugural urban composite development for 17 cities based on 131 indicators across six environments, namely, scale and quality of economic activities, financial capacity, labour market flexibility and economic vibrancy, good governance, effective leadership and social stability, technological advancement and innovation capability, public service standards and quality of life improvement and resource conditions and environmental protection. Findings: The empirical results show that Qingdao, Weihai and Yantai perform well in urban development, while the capital city Jinan only rank in the fourth position. Originality/value: By identifying the relative strengths and weaknesses of each city based on the perspective of ordinary city dwellers, this paper provides appropriate policy recommendations for policymakers to develop and optimise their economies and urban spaces.